On set-valued mappings: M. A. Nasser, Deapo M. AlRahal, Esmail A. M. Alsharabi - جامعة الأندلس للعلوم و التقنية, M. A. Nasser, Deapo M. AlRahal, Esmail A. M. Alsharabi (مجلة الأندلس للعلوم التطبيقية, 2023)
In this work, we discuss several properties and characterizations of continuous set-value mappings, we survey and discuss some weaker forms on this concept, the possibility of dependence of mathematical concepts on the concept of set-value mappings, as linearity, integration, differentiation and measurability etc, also we state and prove some theorems on certain types of set-value mappings.